ETHICAL AWARENESS, PERCEIVED SERIOUSNESS OF WRONGDOING, RATIONALISATION, AND WHISTLEBLOWING INTENTION - Andriati Fitriningrum; Andrey Hasiholan Pulungan; Dini Apti Nirbaya Ahmad (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study examines the impacts of employees’ perceived seriousness of wrongdoing, ethical awareness, and rationalisation on whistleblowing intention. Early research emphasising the effect of outside variables, including opportunity, pressure, and incentive, on the intention to whistleblowing, serves as the driving force of this study. The individual’s internal elements, crucial in determining the intention to whistleblowing, were not disclosed in depth in these earlier studies. The internal employee characteristics that promote whistleblowing are measured by considering the rationalisation, ethical awareness, and perceived seriousness of wrongdoing. A quantitative approach using case scenario questionnaires is used to examine this study. Structural equation modelling (SEM) and partial least squares (PLS)4 assess data from 164 respondents from six government officers in Jakarta, Indonesia. This study indicates that employees’ intentions to report unethical situations and actions are not influenced by the perceived seriousness of the wrongdoing; however, when ethical awareness is present, it can be used to rationalise whistleblowing intentions and actions, thereby mitigating the negative effects of the unethical situation on businesses.